Dermoscopy of Inflammatory Dermatoses (Inflammoscopy) in Skin of Color-A Systematic Review by the International Dermoscopy Society "Imaging in Skin of Color" Task Force - Martyna Sławińska; Jakub Żółkiewicz; Biswanath Behera; Delaney D Ding; Aimilios Lallas; Payal Chauhan; Soumil Khare; Nkechi Anne Enechukwu; Bengu Nisa Akay; Balachandra S Ankad; Yasmeen J Bhat; Abhijeet Kumar Jha; et al. (Mattioli1885, 2023)
Dermoscopic patterns of inflammatory dermatoses (inflammoscopy) have been extensively studied in the recent years, though data on patients with darker phototypes (IV-VI) are sparse. The aims of this systematic review were to summarize the current state of knowledge on inflammoscopy applied to skin of color and provide a standardized nomenclature of reported findings. Besides dermoscopic features, type of setting and magnification, number of cases, and histopathological correlation were analyzed. Eighty-five papers addressing 76 different dermatoses (25 papulosquamous dermatoses, 19 hyperpigmented dermatoses, seven hypopigmented dermatoses, four granulomatous dermatoses, two sclerotic dermatoses, five facial inflammatory dermatoses, and 14 miscellaneous conditions) for a total of 2073 instances were retrieved. Only one study showed a level of evidence of III (cross-sectional study), whereas 10 and 74 displayed a level of evidence of IV (case-control studies) and V (case-series and case-reports), respectively. Moreover, our analysis also highlighted that most of papers focalized on a limited number of dermatoses, with several conditions having only single dermoscopic descriptions. Additionally, few studies compared findings among phototypes belonging to the "skin of color" spectrum. Further studies designed according to a systematic approach and considering the above-mentioned issues are therefore needed.